2019
DOI: 10.1021/jacs.9b01847
|View full text |Cite
|
Sign up to set email alerts
|

Human NEIL3 Gene Expression Regulated by Epigenetic-Like Oxidative DNA Modification

Abstract: The NEIL3 DNA repair gene is induced in cells or animal models experiencing oxidative or inflammatory stress along with oxidation of guanine (G) to 8-oxo-7,8-dihydroguanine (OG) in the genome. We hypothesize that a G-rich promoter element that is a potential G-quadruplex-forming sequence (PQS) in NEIL3 is a site for introduction of OG with epigenetic-like potential for gene regulation. Activation occurs when OG is formed in the NEIL3 PQS loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
72
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 92 publications
9
72
0
1
Order By: Relevance
“…This loss of stability led to the formation of a new G4 structure with an abasic-site-containing loop, which facilitated the binding and stalling of APE1 to the AP site, further stimulating TF binding and activating transcription. [47][48][49][50] The emerging role of 8-oxodG as a transcriptional regulator highlights its biological and health relevance beyond classic toxicity aspects of DNA damage. However, genome-wide associations of 8-oxodG with gene expression and further with pathological processes are not understood due to the lack of precise location information of 8-oxodG in the genome.…”
Section: -Oxodg and Ogg1 Modulate Gene Expressionmentioning
confidence: 99%
“…This loss of stability led to the formation of a new G4 structure with an abasic-site-containing loop, which facilitated the binding and stalling of APE1 to the AP site, further stimulating TF binding and activating transcription. [47][48][49][50] The emerging role of 8-oxodG as a transcriptional regulator highlights its biological and health relevance beyond classic toxicity aspects of DNA damage. However, genome-wide associations of 8-oxodG with gene expression and further with pathological processes are not understood due to the lack of precise location information of 8-oxodG in the genome.…”
Section: -Oxodg and Ogg1 Modulate Gene Expressionmentioning
confidence: 99%
“…In details, OGG1 recruitment on 8-oxo-dG generates an abasic site which unmasks the PQS, leading to the formation of a G-quadruplex where APE1 binds [140] and interacts with transcription factors [141]. This mechanism seems to be particularly relevant in human DNA repair genes, which display PQS enrichment in their promoter and 5′-UTR [142]. Notably, the same mechanism has been shown to be crucial for the expression of several genes such as VEGF [143,144], PCNA [145], NTHL [141], and, more recently, to the DNA repair gene NEIL3 [146].…”
Section: Effect Of 8-oxo-dg On Gene Transcriptionmentioning
confidence: 99%
“…This mechanism seems to be particularly relevant in human DNA repair genes, which display PQS enrichment in their promoter and 5′-UTR [142]. Notably, the same mechanism has been shown to be crucial for the expression of several genes such as VEGF [143,144], PCNA [145], NTHL [141], and, more recently, to the DNA repair gene NEIL3 [146]. Interestingly, another work by Burrows and colleague showed that, when 8-oxo-dG is incorporated in PQSs located in the template strand, the formation of G-quadruplex downregulates gene expression [147].…”
Section: Effect Of 8-oxo-dg On Gene Transcriptionmentioning
confidence: 99%
“…If present in a potential G-quadruplex-forming sequence of promoter, abasic sites can trigger a transition from B DNA to a G-quadruplex structure. This in turn can lead to gene activation via recruitment of purinic/apyrimidinic endonuclease 1 and transcription factors to abasic sites [ 20 ]. H. hepaticus -infected Rag2 −/− /Il10 −/− mice develop colon carcinomas by 4 to 8 months post infection [ 10 , 21 ].…”
Section: Introductionmentioning
confidence: 99%